1953
DOI: 10.1515/znb-1953-0807
|View full text |Cite
|
Sign up to set email alerts
|

2-Jod-östron und 2-Jod-östradiol

Abstract: Durch Jodierung von Östron und Östradiol mit Jod-Quecksilber-acetat in Eisessig werden 2-Jod-östron und 2-Jod-östradiol erhalten.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1959
1959
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The presence in small quantities of the wrong antipode of glutamic acid was also ascertained by experiments of Hillmann and collaborators (19). According to these experiments, small quantities of Dglutamic acid are found in rats after administration per os of various normal proteins from plants or from animals, while, in agreement with findings of Kogl, greater quantities of this aniino acid appear after administration of liver metastases to the test animals.…”
Section: Attempts To Determine By Direct Experiments the Limitasupporting
confidence: 52%
“…The presence in small quantities of the wrong antipode of glutamic acid was also ascertained by experiments of Hillmann and collaborators (19). According to these experiments, small quantities of Dglutamic acid are found in rats after administration per os of various normal proteins from plants or from animals, while, in agreement with findings of Kogl, greater quantities of this aniino acid appear after administration of liver metastases to the test animals.…”
Section: Attempts To Determine By Direct Experiments the Limitasupporting
confidence: 52%
“…Preliminary studies indicated that the solubility of [3H]-I-Hex in pH 7.4 TEA buffer was exceedingly low, several orders of magnitude below that of estradiol (ca. 10-5 M;Hahnel, 1971).…”
Section: Resultsmentioning
confidence: 99%
“…) Aliphatic iodine compounds have a high susceptibility toward substitution and elimination reactions (Gould, 1959); therefore, on the grounds of chemical stability, we considered it preferable to have the iodine bonded to an aryl group. The preparation of both 2-and 4-monoiodo-17/3-estradiol and 2,4-diiodo-17/3-estradiol (Albert et al, 1949;Hillmann-Elies et al, 1953;Nambara et al, 1971; Matkovics et al, 1971) had been reported. Although the iodine in these derivatives appeared to be metabolically stable, these compounds showed either low or negligible uterotrophic activity (Albert et al, 1949;Hillmann-Elies, 1953;Peck et al, 1961), and they were not taken up selectively by the uterus (Albert et al, 1949).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…THE PAST, workers (2,4,5,6) have studied the positions of substituents on the aromatic ring of estratriens. This laboratory would like to confirm these assignments, by means of their nuclear magnetic resonance spectra.…”
mentioning
confidence: 99%